Reflection - Williams, Patricia J. (Columbia Journal of Gender and Law, 2014)
This symposium has been unquestionably the greatest honor of my life. I am deeply grateful to all who planned it, particularly Katherine Franke and Suzanne Goldberg; to each of the remarkable speakers; and to the ever-supportive institutional community of Columbia University. Anything I say beyond that much risks sounding like a bad speech at the Oscars, without benefit of a recuperatively fetching gown. But I am appreciative beyond words for the work invested in shepherding this event into being. It feels as though a truckload of fairy dust had been dumped on me, and suddenly, suddenly . . . little academic wings have sprouted from my shoulders!